THE IMPLEMENTATION OF COLLABORATIVE TECHNIQUE IN TEACHING WRITING TO ENHANCE STUDENTS’ SKILL IN WRITING ENGLISH TEXT - Inayah, Ratih (Direktorat Riset dan Pengabdian kepada Masyarakat, Universitas Bina Darma, 2019)
This study aims to seek insight into the use of Collaborative techniques in enhancing students? interest in writing English and analyzing students' character development in writing skills by applying Collaborative techniques. It employs qualitative descriptive research where the primary data analyzed is the development of students? writing interest and skill during the time of the implementation of the Collaborative Technique. In addition, as secondary data, the analyses of interview and classroom observations were tabulated as supporting primary data. Participants selected by using the Purposive Participant technique. A total of 60 regular students of the 2018 English Education Study Program at one of the private universities in Bandung were involved. The results of the study showed that collaborative technique is successful to increase students? interest in writing English and also help them to develop their own writing skill form before the implementation, during, and after the implementation of Collaborative technique. Thus it can be concluded that collaborative technique affects the process of writing as an individual and group. By doing collaborative techniques in writing English, students tend to be an enthusiast to make a better writing text in English.